PENERAPAN STATIC HEDGE DALAM PENGELOLAAN RISIKO PADA OPSI TIPE BARRIER - ASTUTI, NI MADE NITA; DHARMAWAN, KOMANG; OKA, TJOKORDA BAGUS (E-Jurnal Matematika; Vol 7 No 4 (2018)DO - 10.24843/MTK.2018.v07.i04.p225, 2018)
The barrier option is an option whose payoff depends on whether the underlying asset touches the barrier or not during the lifetime of the option. The determination of the barrier option requires a numerical approach, one of which is the Binomial Tree model. The purpose of this study  is to determine barrier option type down and out call on a static hedging using the Binomial Tree model and compare it with the analytic value. The results show that the increases in strike price would decrease the option value. Moreover, values from 80 periods using the Binomial Tree model for the four strike prices are close to analytic with error less than or equal to 0.00182.